The Effect of Financial Performance on Stock Prices of Companies Listed in the G11 Index (Indonesia Stock Exchange 2024-2025) - Yermias, Merlin; Wakidin, Farida I.S.; Panelewen, Sicilia S. (Journal Research of Social Science, Economics, and Management, 2026)
The purpose of this research is to analyze the effect of Return on Assets (ROA) and Return on Equity (ROE) on stock prices of G11 companies, both partially and simultaneously. This study used a quantitative, associative approach to examine the influence of ROA and ROE on stock prices. Secondary data were obtained from financial reports and stock prices of banking companies listed on the Indonesia Stock Exchange for the 2024–2025 period. The sample was determined using purposive sampling, resulting in 18 companies with 36 observations. Data analysis was performed using SPSS through descriptive statistical tests, classical assumption tests, and multiple linear regression. Hypothesis testing was performed using the t-test, F-test, and coefficient of determination (R²). The results indicate that ROA has a small and inconsistent effect on stock prices, and is therefore not a primary consideration for investors. Conversely, ROE is shown to be more influential, reflecting investors’ focus on a company’s ability to generate returns on capital. Simultaneously, ROA and ROE influence stock prices, but other external factors, such as economic conditions and interest rates, also influence stock price movements.